2021
DOI: 10.3389/fphar.2021.631293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Intravenous and Oral Sequential Treatment With Voriconazole for Candida Central Nervous System Infection in Six Premature Infants

Abstract: Objective: The aim of the study was to observe the clinical efficacy and safety of intravenous and oral sequential treatment with voriconazole for Candida central nervous system (CNS) infection in premature infants.Methods: The study included retrospective analysis of the clinical data of six premature infants with Candida CNS infection admitted to the neonatology department in Shanghai Children’s Hospital between November 2016 and November 2019. By reviewing the characteristics of voriconazole based on the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…1 Amphotericin B is the preferred for treatment of Candida meningitis, although fluconazole can be used in mild cases or when amphotericin B is not tolerated. 2 According to previous case reports, Candida meningitis can be well-managed using standardized treatment with fluconazole alone, 3 voriconazole, 4,5 and amphotericin B combined with flucytosine. 3,6 Clinical studies have also shown that amphotericin B colloidal dispersion (ABCD) has similar efficacy 7 and less nephrotoxicity 8 compared to liposomal amphotericin B with respect to antifungal activity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Amphotericin B is the preferred for treatment of Candida meningitis, although fluconazole can be used in mild cases or when amphotericin B is not tolerated. 2 According to previous case reports, Candida meningitis can be well-managed using standardized treatment with fluconazole alone, 3 voriconazole, 4,5 and amphotericin B combined with flucytosine. 3,6 Clinical studies have also shown that amphotericin B colloidal dispersion (ABCD) has similar efficacy 7 and less nephrotoxicity 8 compared to liposomal amphotericin B with respect to antifungal activity.…”
Section: Introductionmentioning
confidence: 99%